Industrial Harmony In Modern Japan: The Invention Of A Tradition - Perline, Martin M. (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Industrial Harmony In Modern Japan: The Invention Of A Tradition," by W. Dean Kinzley.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z